2021
DOI: 10.1002/cpdd.913
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Gepotidacin in Subjects With Normal Hepatic Function and Hepatic Impairment

Abstract: Gepotidacin is a novel triazaacenaphthylene bacterial topoisomerase inhibitor. This phase 1 nonrandomized, open-label, multicenter, 2-part study evaluated the pharmacokinetics, safety, and tolerability of oral gepotidacin 1500 mg in 3 different hepatic settings (normal, moderate impairment, and severe impairment). Gepotidacin was safe and generally tolerated in all subjects. Compared to subjects with normal hepatic function, gepotidacin plasma area under the plasma concentration-time curve from time 0 to infin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 12 publications
6
14
0
Order By: Relevance
“…19 No clinically significant QT prolongations were noted in any of the three studies, consistent with previous data. 9,11,12,[14][15][16] In conclusion, the safety and PK profile of gepotidacin has been well-characterized across a wide range of doses in healthy participants aged greater than or equal to 18 years, with GI AEs (primarily mild-to-moderate nausea and diarrhea) commonly reported. These GI AEs are alleviated when oral gepotidacin is taken with food.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…19 No clinically significant QT prolongations were noted in any of the three studies, consistent with previous data. 9,11,12,[14][15][16] In conclusion, the safety and PK profile of gepotidacin has been well-characterized across a wide range of doses in healthy participants aged greater than or equal to 18 years, with GI AEs (primarily mild-to-moderate nausea and diarrhea) commonly reported. These GI AEs are alleviated when oral gepotidacin is taken with food.…”
Section: Discussionmentioning
confidence: 87%
“…Consistent with previous studies, there were no other clinically important changes in laboratory parameters, or vital signs in these studies. 9,11,12,[14][15][16] The most common AEs among participants who received gepotidacin across all studies were GI (study 1, 10/36 [28%]; study 2, 35/54 [65%]; and study 3 part 3, 19/29 [66%]). Previous studies of gepotidacin have reported similar results, with the most common AEs of diarrhea, nausea, flatulence, and abdominal pain, which resolved by the end of the study and were not related to C. difficile infection.…”
Section: Discussionmentioning
confidence: 99%
“…An f AUC 0–24 /MIC ratio of 275 prevented resistance amplification in an in vitro hollow-fiber model ( 30 ). Finally, data from phase I and phase IIa clinical studies with GEP oral dosing of either a single dose or 5 days BID of 1,500 mg showed high GEP exposures in urine in both healthy volunteers and participants with uUTIs ( 8 , 35 , 36 , 38 , 41 ), with the minimum observed GEP urine levels resulting in urine AUC 0–24 /MIC values exceeding the model-derived nonclinical efficacy and resistance suppression PK/PD targets. The clinical significance and translation of these findings in the treatment of uUTI still need to be further understood.…”
Section: Summarizing Dose Regimen Selection For Phase III Studies In ...mentioning
confidence: 95%
“…GEP exposure in the urine was also examined in a phase I study (ClinicalTrials.gov identifier NCT03562117) in participants with hepatic impairment ( Table 1 ). Values for GEP urinary exposure and the total amount excreted into the urine increased with increasing severity of hepatic impairment ( Table 1 ) ( 38 ). Urine GEP concentrations remained high for 12 h postdose in participants with normal and impaired hepatic function.…”
Section: Clinical Pharmacokinetic/pharmacodynamic Analysesmentioning
confidence: 99%
“…This is because GEPO’s binding site is close to but distinct from FQ, thus allowing for its activity against FQ-resistant strains (8). Clinical safety of GEPO has been evaluated in healthy human subjects and subjects with renal impairment in phase I clinical trials (NCT02202187, NCT02729038) by both intravenous and oral formulations and has been found to be safe (9, 10, 11, 12). It is currently under various clinical trials for the treatment of sexually transmitted infections (STI) caused by N. gonorrhoeae as well as acute bacterial skin and skin structure infections (ABSSSI) (13, 14).…”
Section: Introductionmentioning
confidence: 99%